2007
DOI: 10.1007/s11664-007-0216-3
|View full text |Cite
|
Sign up to set email alerts
|

Platinum and Rhodium Silicide–Germanide Optoelectronics

Abstract: Since the introduction of SiO 2 /Si devices in the 1960s, the only basic change in the design of a MOSFET has been in the gate length. The channel thickness has fundamentally remained unchanged, as the inversion layer in a silicon MOSFET is still about 10 nm thick. Bipolar transistor base widths have been of sub-micron dimensions all this time. It is time for a new property to be exploited in concert with the high mobility strained-silicon channels and silicon-germanium alloys. This property is the inherently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Moreover, SBD can be easily integrated with Schottky-bipolar circuits providing superior radiation resistance. However, Schottky-barrier photodiode based on PtSi formed on p-type silicon have certain drawbacks mainly related to increased dark current at increased operating wavelength and suppressed quantum yield by non-radiative photon absorption [15]. It has been demonstrated that these drawbacks can be overcome by replacing PtSi with RhSi in the photo-detector [15].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, SBD can be easily integrated with Schottky-bipolar circuits providing superior radiation resistance. However, Schottky-barrier photodiode based on PtSi formed on p-type silicon have certain drawbacks mainly related to increased dark current at increased operating wavelength and suppressed quantum yield by non-radiative photon absorption [15]. It has been demonstrated that these drawbacks can be overcome by replacing PtSi with RhSi in the photo-detector [15].…”
Section: Introductionmentioning
confidence: 99%
“…However, Schottky-barrier photodiode based on PtSi formed on p-type silicon have certain drawbacks mainly related to increased dark current at increased operating wavelength and suppressed quantum yield by non-radiative photon absorption [15]. It has been demonstrated that these drawbacks can be overcome by replacing PtSi with RhSi in the photo-detector [15]. In the past, RhSi based photodiodes were studied extensively by Lepster et al, [15] and were employed in low-power bipolar transistor circuits containing RhSi/n-Si and RhSi/p-Si junctions of high and low barrier heights [16].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations